Menentukan Strategi Manajemen Pada UMKM Dimsum untuk Mengembangkan Bisnis - Permana, Ilham; Josephine, Josephine; Hadiantini, Ratih (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2022)
The COVID-19 pandemic has had a significant impact on the MSME sector in Indonesia, with a drastic decline in revenue, as 82.9% of business owners experienced negative effects (Katadata Insight Center, 2020). One of the affected MSMEs is a culinary business, specifically a Dim Sum business. This study aims to identify the key issues in business management, including human resources, marketing, and financial management, as well as provide strategic recommendations to support business sustainability. The research method used is descriptive qualitative, involving observation, interviews, and analysis using SWOT and TOWS Matrix. The results indicate that the Dim Sum MSME faces challenges such as lack of product innovation, limited implementation of digital marketing strategies, absence of branding and halal certification, and issues in financial management and human resources. Based on the analysis, it is recommended that the business establish its own brand, register for halal certification, and utilize dedicated social media for business promotion. Through this community service program, the business owner is expected to implement the proposed solutions to improve competitiveness and business sustainability in the face of dynamic market changes. This research provides important contributions to supporting MSME adaptation to the challenges of the digital era and post-pandemic recovery.